Education, Financial Stress, and Trajectory of Mental Health During the COVID-19 Pandemic. (July 2022) - Jiang, Yanping; Zilioli, Samuele; Balzarini, Rhonda N.; Zoppolat, Giulia; Slatcher, Richard B.
In this preregistered study, we examined educational disparities in the trajectory of mental health during the COVID-19 pandemic and whether such educational disparities would be mediated by financial stress associated with the pandemic. Data were drawn from the Love in the Time of COVID project ( N = 2, 204; four waves collected between March and June 2020). Results suggested educational disparities in eudaimonic well-being, negative affect, and psychological distress and showed significant associations between lower education and worse mental-health outcomes at baseline. However, education did not amplify mental-health disparities over time and exhibited no associations with the rates of change in mental health. Financial stress mediated the associations between education and mental health at baseline, and there were no temporal variations in the mediation effect. These results highlight persistent educational disparities in mental health, and such educational disparities may be partially explained by financial stress associated with the COVID-19 pandemic.